Cuboid-navicular coalition in pediatrics: a systematic review and report. Issue 2 (March 2016) - Worsham, Jacob; Neal, Kevin; Hahn, George; Moran, Elizabeth; Klassen, Christopher
Abstract : Background: Tarsal coalition is a rare condition affecting less than 1% of the US population. The onset of symptoms is thought to be due to previously fibrous or cartilaginous coalitions ossifying, becoming more rigid, and becoming more painful. Nine clinical case reports have been presented in the literature over the last half century. The purpose of our study was to provide a thorough review of the literature and present two cases from our practice. Methods: We performed a systematic review of the MEDLINE database using OvidSP and PubMed resources. A total of 14 articles with 17 total patients were found. Only reports that had patients age 18 or younger were accepted. This eliminated six patients and seven coalitions, leaving a total of 11 patients and 17 coalitions. Results: Including this study, a total of 13 patients and 21 coalitions were used for analysis. The average age at onset of symptoms was 14.7 yr, and the average prodrome was 20 mo. Conservative management was effective in three patients; ten opted for surgical management. Surgical intervention was considered successful in 80% of patients. Conclusions: Cuboid-navicular coalitions are rare but should be in the differential diagnosis for unexplained foot pain. In our patients and through our literature review, we found that CT and MRI are equally effective in identifying coalitions, and MRI is superior for any synchondrosis or synostosis. Bone scan is unnecessary in the diagnosis of this condition. Conservative management is still the initial line of treatment, but surgical intervention has shown success.